Terrain Analysis Along Major Roads in University of Lagos Campus - Abiodun, O. E.; Bello, I. B.; Atteh, A. P.; Sulaimon, B. A. (Journal of Spatial Information Sciences, 2025)
Investigation into surface level is an exercise that provides the required data for lasting solutions to environmental and engineering problems. Flooding is a major environmental problem that causes unquantifiable damages and requires engineering solutions. University of Lagos is located close to the Lagoon making many areas within the University to be susceptible to flooding. Investigation into the surface level on the major roads of the University of Lagos will provide information for a better understanding of flooding on campus. This study, therefore, carried out the terrain analysis of major roads within the University of Lagos to identifying flood prone areas along the road. Automatic level was used in a levelling exercise along the roads. Observations were taking at every 25 meter intervals at the two sides of the roads as well as the center lines of the roads. Observed data were processed and accuracy obtained agrees with a second order levelling. Results were presented in longitudinal sections using the central road data observations. Contour lines and flow direction map were also produced using both center line and road side observations. A Digital Terrain Model of the major roads was produced and a 3D wireframe that shows the terrain formation along the major roads. Analysis of the results revealed flood prone spots. It was concluded that another study of the entire University of Lagos as well as the analysis of the drainage system in the immediate vicinity of the campus is required to proffer a lasting solution to flooding on the campus.
Keywords: Terrain; Flood; Road Network; Analysis; University of Lagos